Patterns of Medicinal Plant Use in Traditional Healing Practices in Semerap, Kerinci Regency - Lucya Audini Lorensa; M. Eval Setiawan; Emayulia Sastria; Hendra Lardiman (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
This study aimed to identify the medicinal plant species utilized by the community, describe the plant parts used along with their processing techniques, and examine the implications for preserving the associated local wisdom. The study employed a descriptive qualitative approach using observation and in-depth interviews with five key informants selected purposively, including community leaders and traditional practitioners. The sample size was determined based on the principle of data saturation, which was reached when interviews no longer generated new information or themes relevant to the research focus. Data were analyzed using thematic procedures consisting of data reduction, data display, and conclusion drawing. The findings showed that the people of Semerap Village use a variety of medicinal plant species, with a clear preference for leaves over other parts such as rhizomes, fruits, and bark. The most commonly applied preparation method was decoction (boiling) for oral consumption, followed by topical application through pounding. In addition, traditional healing practices integrated herbal remedies with spiritual modalities, such as prayer or ruqyah, reflecting the local belief system. These plants were used to treat a wide range of health conditions, from minor ailments to chronic diseases. This study provides crucial documentation of local ethnobotanical knowledge, enriching regional data while supporting community-based efforts to conserve traditional knowledge.